The other side of glamour : the left-wing studio network in Hong Kong cinema in the Cold War era and beyond - Lee, Vivian P. Y., 1966- (Global film studios., 2020)
Hong Kong cinema has been a pre-eminent form of local entertainment and a site of ideological contentions propelled by colonial, national and international politics at different historical junctures. The Other Side of Glamour is a study of the historical development of the left-wing film establishment in Hong Kong.